2016
DOI: 10.1159/000444327
|View full text |Cite
|
Sign up to set email alerts
|

Ocular Erythropoietin Penetration after Subconjunctival Administration in Glaucomatous Rats

Abstract: Purpose: The present study aimed to determine whether the subconjunctival administration of recombinant human erythropoietin (rHuEPO) reached the retina in glaucoma conditions. After subconjunctival rHuEPO administration, in a rat glaucoma model, erythropoietin (EPO) distribution in the rat's retina was studied by immunohistochemistry. Methods: Female Wistar Hannover albino rats (n = 15) were divided into 2 groups, control (n = 3) and treated (n = 12). The animals' unilateral glaucoma was induced by coagulatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 26 publications
2
6
0
Order By: Relevance
“…Since glaucoma is a chronic disease, multiple treatments to protect RGCs are required, and using the subconjunctival route seems to be more feasible. Concerning subconjunctival EPO administration, we also demonstrated that rHuEPO reached the RGC layers when administered by this route both in physiological and glaucomatous conditions without significant unwanted side effects [20,21].…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Since glaucoma is a chronic disease, multiple treatments to protect RGCs are required, and using the subconjunctival route seems to be more feasible. Concerning subconjunctival EPO administration, we also demonstrated that rHuEPO reached the RGC layers when administered by this route both in physiological and glaucomatous conditions without significant unwanted side effects [20,21].…”
Section: Discussionmentioning
confidence: 69%
“…It has been previously demonstrated that EPO reached the RGC layer both in physiological and glaucoma conditions in a rat animal model when administered through the subconjunctival route [20,21]. The subconjunctival route for EPO ocular administration has been demonstrated to be a safe and easy procedure with few associated risks [19,22].…”
Section: Introductionmentioning
confidence: 99%
“…A recent review article describes the antiapoptotic, angiogenic, antiinflammatory, antioxidant, and neuroprotective effects of EPO in the ocular tissues, including the retina [25]. Subconjunctival administration of EPOβ in solution (NeoRecormon ® ) in rats was already performed by our team, which proved that EPOβ reached the inner layers of the retina with one single dose [8][9][10]. Due to the minor-invasive nature of this route of administration, it was selected to administer CS/HA-EPOβ nanoparticles to rats to assess its safety and ocular penetration in healthy animals.…”
Section: Discussionmentioning
confidence: 99%
“…The nanoparticles allowed EPOβ to trespass the outer layers of the ocular globe to reach the inner layers after only 12 h. This fast delivery to the retina might be attributed to the hydrophilic nature of EPOβ, due to its high degree of glycosylation [26], which means that the preferential route of EPOβ absorption would be the conjunctival-scleral pathway, as it is more successful to the posterior segment delivery [35]. In previous studies, EPOβ was also detected in the retina after subconjunctival administration of a commercial solution (NeoRecormon ® ) [8,9]. Moreover, in this study, EPOβ was likewise detected in the corneal endothelium and ciliary body, and the conjunctival-scleral absorption would be unlikely to contribute to this finding due to the presence of the blood-aqueous barrier [36].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation